E-Module Mangrove Ecotourism: Difference and Relationship Perception, Interest, and Environment Character Care Elementary Students - Asrial, Asrial; Syahrial, Syahrial; Kurniawan, Dwi Agus; Chen, Diki; Wulandari, Mashelin (Jurnal Ilmiah Peuradeun, 2022)
This research aimed at seeing how the level of perception, interest in learning, and the character of students' environmental care; this study also sees the difference after using the mangrove ecotourism e-module. This quantitative research used the variables of students' perceptions, interests, and environmental care. The sample used was 120 students in 3 different elementary schools, the sampling technique used was simple random sampling. Data analysis used descriptive statistics, ANOVA test, and correlation test. From the results obtained, it can be seen that the students of Islamic boarding schools have the lowest perceptions and interest in learning, namely 46.65 and 32.92. However, to protect the environment, the number of students in Islamic boarding schools is higher than in other students. In the Anova test, elementary school children had different perceptions and interests in learning, while for the character of caring for the environment between Madrasah and Islamic Boarding School children. Other results also showed that perception had a relationship of 20.6% with student interest in learning and 66% with concern for the student's environment. This study's conclusion showed that the e-module can increase the interest and character of students' environmental care.